Power-driven tower cranes for building and engineering construction - British Standards Institution (London BSI, 1974)
Tower cranes, Cranes, Lifting equipment, Electrically-operated devices, Building sites, Jib cranes, Construction equipment, Travelling cranes, Designations, Stability, Safe working load, Structural design, Design, Joints, Stress, Tracks (materials handling equipment), Wire ropes, Steel-wire ropes, Breaking load, Lifting tackle, Hoisting drums, Dimensions, Pulleys, Gear drives, Mechanical components, Brakes, Machine guards, Cabs, Electrical equipment, Control devices, Electric control equipment, Electrical protection equipment, Overload protection, Isolator switches, Electric cables, Hydraulic equipment, Occupational safety, Performance testing, Painting, Certificates of conformity, Legislation, Definitions, Velocity, Design calculations, Efficiency, Tensile loading
Withdrawn
Cross References BS 302, BS 327, BS 350, BS 357, BS 436, BS 466, BS 545, BS 587, BS 649, BS 721, BS 765, BS 775, BS 800, BS 833, BS 1486:Part 1, BS 1486:Part 2, BS 1757, BS 1761, BS 2059, BS 2452, BS 2521 & 2523, BS 2525-27, BS 2573:Part 1, BS 2573:Part 2, BS 2613, BS 2771, BS 2903, BS 3032, BS 3037:Part 1, BS 3139, BS 3294, BS 3535, BS 3550, BS 3551, BS 3579, BS 4235, BS 4395, BS 4533:Part 2:Section 2.3, BS 4604, BS 6007, BS 6116, BS 6500, CP 1013, CP 1017, CP 3010, Construction (Lifting Operations) Regulations 1961, Construction (Lifting Operations) Reports Order 1962, Construction (Lifting Operations) Prescribed Particulars Order 1962, Construction (Lifting Operations) Certificates Order 1961, Construction (General Provisions) Regulations 1961, S.I. 1966/94, Construction (Working Places) Regulations 1966, Electricity Regulations 1908, Electricity (Factories Act) Special Regulations 1944, Factories Act, 1961, Chains, Ropes and Lifting Tackle (Register) Order 1938, Lifting Machines (Particulars of Examinations) Order 1963, Docks Regulations 1934, Shipbuilding and Ship-repairing Reg
Keywords: Cranes -- Standards